E-learning design in Malaysian higher educational institutions: principles and guidelines - Alberto Aning; Aslina Baharum (Journal of Hunan University (Natural Sciences）, 2020)
E-learning is a recent learning tool that can be engaged with via websites through the Internet. Therefore, there is a need to identify various factors that will affect students while accessing learning resources from websites. In Malaysia, many educational institutions will be required to implement or improve the e-learning techniques in their education system. A specific guideline on the design process of e-learning websites to accommodate developers is required. This paper aimed to identify and examine the basic principles, user interface design guidelines, and challenges of integrating e-learning in Malaysian higher educational institutions. The results of the study indicate that there is no specific design standard for e-learning in Malaysian higher educational institutions. The basic components of e-learning include infrastructure, the platform, and content development as outlined by the Malaysian Higher Education Ministries. The design process of user interface design for e-learning would benefit from adding localization elements to be included as a guideline.